Biallelic mutations in sord are a common cause of potentially treatable genetic neuropathy. Issue 6 (27th May 2022) - Cortese, Andrea; Zhu, Yi; Rebelo, Adriana; Negri, Sara; Courel, Steve; Abreu, Lisa; Bacon, Chelsea J; Bai, Yunhong; Bis-Brewer, Dana M; ,
Abstract : Introduction: As opposed to CMT1, for which over 90% of cases have mutations in known genes, only 20–30% of CMT2/dHMN patients receive a genetic diagnosis. Since up to 70% of CMT2 and dHMN cases are sporadic, identifying candidate pathogenic genes from single cases remains challenging also for next-generation sequencing techniques. Methods: We took advantage of the largest collection of over 1, 100 CMT patients in whom WES and/or WGS has been performed in the GENESIS analysis platform. We specifically looked for genes for which significant DNA variants are present in multiple families as well as for individual alleles overrepresented in CMT cases. Results: We identified 45 cases from 38 families across multiple ethnicities, carrying a particular nonsense mutation in SORD, c.753delG;p.Ala253GlnfsTer27, either in homozygous or compound heterozygous state with a second variant. With an allele frequency of 0.004 in healthy controls, the p.Ala253GlnfsTer27 variant represents one of the most common pathogenic alleles in humans. SORD is an enzyme that converts sorbitol into fructose, in the two-step polyol pathway that has been implicated in diabetic neuropathy. In patient-derived fibroblasts, we find a complete loss of SORD protein and increased intracellular sorbitol. Also, as a biomarker, serum fasting sorbitol level was over 100 times higher in patients compared to healthy individuals. In Drosophila, we show that loss of SORD orthologues causes synaptic degeneration and progressive motor impairment. Reducing the polyol influx by treatment with aldose reductase inhibi- tors normalized intracellular sorbitol levels in patient fibroblasts and in Drosophila, and also dramatically ameliorated motor and eye phenotypes. Conclusions: We demonstrate biallelic mutations in sorbitol dehydrogenase (SORD) as the most frequent recessive form of hereditary neuropathies. These findings establish a potentially treatable cause in a sig- nificant fraction of patients with inherited neuropathies and may contribute to a better understanding of the pathophysiology of diabetic neuropathy. andrea.cortese@ucl.ac.uk